Types of Marketing Collateral Your Practice Needs for 2023 - Duncan, Zoey (Canadian Journal of Optometry, 2022)
The right mix of marketing materials for your practice depends on who your patients are and what your business growth goals are. Your 2023 marketing plan can and should include a combination of different marketing collateral to bring your goals to fruition in the short and long-term.